DETERMINANTS OF FARMER-HERDER CONFLICTS AMONG RURAL HOUSEHOLD IN BAUCHI STATE, NIGERIA - Balarabe, M.B.; Abdullahi, S.; Bala, A.H. (Nigerian Journal of Agriculture and Agricultural Technology, 2024)
The study examined the determinant of farmer-herder conflicts among rural households in Bauchi State, Nigeria. A multistage sampling technique was used in selecting 240 respondents for the study. Data were collected through the administration of structured questionnaires and analyzed using both descriptive and inferential statistics. The result from the findings revealed that 30%, 28.3% and 21.3% of the respondents were within the ages of 30-40 years, 41-51 years and 52-62 years respectively, with a mean age of 46 years. The result further shows that majority (60.4%) of the respondents had household size of 1-6 persons with a mean 6 persons per households. On the other hand the result shows that 36.7% and 34.2% of the respondents had a farm size of 2ha and 3ha of land with a mean farm size of 2.4ha. The result also reveals that 31.3% and 22.9% of the respondents had a farming experience of 15-20 years and 9-14 years with an average of 16 years. The result also shows that 36.3% and 28.7% of the respondents had a herd size of 41-68 cattle and 13-40 cattle with a mean of 64 cattle per herd. Also, the respondents agreed that crop damage by cattle, land encroachment and inadequate grazing reserves were the major causes of farmer-herder conflict as indicated by the mean scores of 4.2, 4.1 and 4.4 respectively. The results of regression revealed that, marital status and herd size were positive and significant (P<0.05) in influencing farmer-herder conflicts in the study area. The major constraints to conflict management in the study area were ineffective/negative communication pattern, weak institutions and corruption/poverty which were the major causes of conflict which were ranked 1st, 2nd and 3rd respectively. The study concluded that, marital status and farm size of the respondents were the factors that influence conflict among the respondents in the study area. The need to use the mitigation strategies and conflict resolution mechanism cannot be over emphasized because it has potentials for improving food security as well as peace and harmony among the rural farming households in the study area. Based on the constraints highlighted the study recommended that, farmers and herders associations should provide an avenue for teaching and learning of local languages to fill the gap in communication, traditional and religious leaders should be up and doing in terms of mitigating conflicts at early stages and government should improve and employ more extension personnel to improve respondents’ level of production and living standards.